2008
DOI: 10.3748/wjg.14.4583
|View full text |Cite
|
Sign up to set email alerts
|

Direct invasion to the colon by hepatocellular carcinoma: Report of two cases

Abstract: Although hepatocellular carcinoma (HCC) is a common tumor, direct invasion of the gastrointestinal tract by HCC is uncommon. Recently, we encountered two cases of HCC with direct invasion to the colon. The first patient was a 79-year-old man who underwent transarterial chemo-embolization (TACE) for HCC 1.5 years prior to admission to our hospital. Computed tomography (CT) showed a 7.5-cm liver tumor directly invading the transverse colon. Partial resection of the liver and transverse colon was performed. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Although this occurrence was observed in approximately 10% of patients with HCC in a study of postmortem examinations, the incidence is reported to be 0.5% and 2% of clinical HCC cases (6,7). The organs involved included the duodenum, stomach, colon, or jejunum (8).…”
Section: Discussionmentioning
confidence: 99%
“…Although this occurrence was observed in approximately 10% of patients with HCC in a study of postmortem examinations, the incidence is reported to be 0.5% and 2% of clinical HCC cases (6,7). The organs involved included the duodenum, stomach, colon, or jejunum (8).…”
Section: Discussionmentioning
confidence: 99%
“…When intrahepatic lesions are well controlled and in good hepatic reserve, symptomatic or life-threatening metastasis should be treated. (2,3) RFA is technically difficult because of its high risk of perforation, (11) and TAE and TACE are not effective in treating HCC with GI tract metastasis. (11) Surgical resection may be the most effective treatment option for GI tract metastasis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…(2,3) RFA is technically difficult because of its high risk of perforation, (11) and TAE and TACE are not effective in treating HCC with GI tract metastasis. (11) Surgical resection may be the most effective treatment option for GI tract metastasis of HCC. According to Fujii et al, the median survival time of patients with GI tract invasion treated using surgical resection is longer than those who receive nonsurgical and supportive treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations